The Consequences of Preparation and Impulsivity in The Three Little Pigs - Suawah, Belinda Angela; Wola, Fristo Timothy; Miarso, John Prince; Miarso, Jessie Queen; Siregar, Theofanny Gracia (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2026)
This study analyzed The Three Little Pigs through the theoretical framework of Maria Tatar’s Moral Development Theory (2009), identifying the consequences of preparation vs. impulsivity, the value of preparation for young audiences, and the role of a narrative device in testing preparedness and impulsivity. The story focuses on the three pigs, who moved out from their parents house to build their own, then the Big Bad Wolf destroyed the first two pig’s houses that were made of sticks and straws, but when it comes to the third pig’s house, the wolf could not destroy it because it was made of stones. The finding reveals: 1) Preparation leads the third pig to safety and success, meanwhile the first two pigs have to experience the consequences of impulsivity which is the wolf’s attack. This outcome demonstrates the moral lesson of the tale: the importance of foresight, diligence, and hard work. The story highlights how careful preparation and effort lead to security and success, while impulsivity and shortcuts result in vulnerability and failure. 2) The narrative’s outcome shows the importance of preparation and how impulsivity can lead to negative consequences. The first two pigs were rushing to construct their homes which resulted in their houses getting destroyed. Meanwhile, the third pig was patient and didn’t rush things which led to the house being safe from the wolf. 3) The big bad wolf serves as a narrative device to test the resilience of the three little pigs’ houses, figuring out who is the best at planning to build.